PERSEPSI ANAK TAMAN KANAK-KANAK TK INTEGRAL YAA BUNAYYA TENTANG KEBIASAAN MERAPIKAN MAINAN SETELAH BERMAIN KAITANNYA DENGAN KESEHATAN FISIK DAN MENTAL ANAK - Kiki Rizki Aulia; Sri Rahmawati; Mariati (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Encouraging young children to tidy up their toys after play is more than a simple routine; it is a vital practice in early character development that nurtures lifelong discipline and a sense of responsibility. This study seeks to look closely at how kindergarten children perceive the act of packing away their toys and how they make sense of this daily expectation. Using a qualitative, descriptive approach, the research focused on the lived experiences of children aged 5–6 at TK Integral Yaa Bunayya. Insights were gathered through immersive observations, gentle interviews adapted to the children’s developmental communication styles, and documentation. The data were then analyzed through a reflective process of reduction, display, and thematic synthesis. The findings highlight that most children view tidying up as a way to respect the boundaries set by their teachers and parents, while also taking pride in keeping their play environment clean and orderly. Interestingly, many children showed deep empathy, understanding that putting toys back where they belong helps their peers find them easily and keeps their shared space comfortable. However, for some children, the task is still felt to be less enjoyable, meaning they still rely on the patient guidance and support of their educators. Ultimately, this study shows that when children hold a positive view of these small responsibilities, it deeply enriches their growth in discipline, accountability, and social awareness. For these positive habits to truly take root, a consistent and supportive partnership between home and school is essential.